2019
DOI: 10.1021/acs.jpca.9b09274
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Electronic Transitions of Polyethylene Glycol upon the Formation of a Coordinate Bond with Li+, Studied by ATR Far-Ultraviolet Spectroscopy

Abstract: This study investigates the electronic transitions of complexes of lithium with polyethylene glycol (PEG) by the absorption bands of solvent molecules via attenuated total reflectance spectroscopy in the far-UV region (ATR−FUV). Alkali-metal complexes are interesting materials because of their functional characteristics such as good ionic conductivity. These complexes are used as polymer electrolytes for Li batteries and as one of the new types of room-temperature ionic liquids, termed solvation ionic liquids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…In another study, alkali metal complexes composed of a Li salt and PEG were investigated, and it was found that the absorption bands of PEG 17 at 155 and 177 nm shifted higher in energy because of the formation of a complex between Li þ ions and PEG. 19 Further, the intensity of the band at 177 nm decreased with increasing Li salt concentration. Thus, these results can be used to understand the ionic environment around PEG.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In another study, alkali metal complexes composed of a Li salt and PEG were investigated, and it was found that the absorption bands of PEG 17 at 155 and 177 nm shifted higher in energy because of the formation of a complex between Li þ ions and PEG. 19 Further, the intensity of the band at 177 nm decreased with increasing Li salt concentration. Thus, these results can be used to understand the ionic environment around PEG.…”
Section: Introductionmentioning
confidence: 94%
“…Morisawa et al focused on the electronic states of polymers such as nylon, 16 polyethylene glycol (PEG), 17 polyhydroxy butylate (PHB), nanocomposites of PHB and graphene, 18 and complexes of PEG and lithium ions. 19,20 In these studies, the electronic transitions of polymers were investigated by comparing the ATR-FUV spectra and simulated spectra obtained using quantum chemical calculations, thus revealing the potential usefulness of ATR-FUV for polymer analysis. For example, the FUV spectra of a series of nylon polymers have been reported previously, 16 and the major absorption bands at around 150 and 200 nm were assigned to the s-3p y Rydberg and p-p* transitions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nami UENO,* Tomonari WAKABAYASHI,** and Yusuke MORISAWA** † suggesting that the absorbance of the 177 nm band reflects the concentrations of free COC in the solutions. 12 Therefore, the ATR-FUV spectra of the binary solutions display an LiTFSI concentration dependency, and the coordination number can be determined using the reaction model described below.…”
Section: Determining the Coordination Number Of LI + And Glyme Or Poly(ethylene Glycol) In Solution Using Attenuated Total Reflectance-famentioning
confidence: 99%
“…We observed a reflection absorbance at approximately 170 nm due to an n-Rydberg (Ryd) 3s transition, which was correlated to a concentration of oxygen in ether not involved in a coordination bond. 12 As ATR-FUV provided us the opportunity to observe the formation of coordination bonds in PEG ether groups, an analysis of the reflection absorbance of solutions of Li + by ATR-FUV should allow for the determination of the coordination number of Li + .…”
mentioning
confidence: 99%
See 1 more Smart Citation